TINJAUAN HUKUM ATAS PENYALAHGUNAAN DATA BANTUAN SOSIAL DI MASA PANDEMI COVID-19 - Disurya, Ramanata; Suryati, Suryati (Faculty of Law, University of Palembang, 2021)
Social assistance in the form of money, goods or services is very valuable in the midst of disasters, especially in the Covid-19 pandemic. It becomes highly anticipated by the affected communities as well as tempting things to be abused for irresponsible people. This study aims to find out how the legal review of the misuse of social assistance data during the Covid-19 pandemic. The research method used in this study is the normative method of law. The results of this study are , (1) all forms of misappropriation of social assistance funds are punishable under Article 43 paragraph (1) of Law No. 13 of 2011, (2) concerning the hoarding of social assistance with the purpose of benefiting themselves punished according to Article 3 of Law No. 31 of 1999 concerning the Eradication of Corruption crimes jo